2020
DOI: 10.1556/004.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Influences of tolfenamic acid and flunixin meglumine on the disposition kinetics of levofloxacin in sheep

Abstract: The pharmacokinetics of levofloxacin (4 mg/kg), administered both alone and in combination with tolfenamic acid (2 mg/kg) and flunixin meglumine (2.2 mg/kg), was established after intravenous administration in sheep. Plasma levofloxacin concentrations were assayed by high-performance liquid chromatography and analysed according to the two-compartment open model. Following the administration of levofloxacin alone, the mean distribution half-life, elimination half-life, total clearance, volume of distribution at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Therefore, the high plasma concentration of CFQ in combination with ketoprofen may be a reason for low V darea /F calculation. Similar results have been reported in previous studies (Altan et al, 2020;Durna Corum et al, 2020;Oh & Han, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the high plasma concentration of CFQ in combination with ketoprofen may be a reason for low V darea /F calculation. Similar results have been reported in previous studies (Altan et al, 2020;Durna Corum et al, 2020;Oh & Han, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Previous unpublished studies in our laboratory have demonstrated that flunixin meglumine pretreatment diminishes the number of ewes that succumb to endotoxemia within the first 24 hours following IV administration of campylobacter. This drug inhibits cyclooxygenase thereby decreasing prostaglandin synthesis [31,32]. In one report in sheep, flunixin meglumine slowed the elimination and increased plasma concentrations of levofloxacin [31].…”
Section: Plos Onementioning
confidence: 99%
“…This drug inhibits cyclooxygenase thereby decreasing prostaglandin synthesis [31,32]. In one report in sheep, flunixin meglumine slowed the elimination and increased plasma concentrations of levofloxacin [31]. It was speculated that inhibition of prostaglandin synthesis in the kidneys by flunixin meglumine caused reduced renal blood flow and a reduced glomerular filtration rate leading to decreased excretion of the antibiotic via urine [31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…These changes may lead to the development of resistance to antibiotics, the emergence of undesirable effects, and a suboptimal level of drug exposure, leading to failure in the treatment of infection [28,29]. Although there are many studies investigating the effects of NSAIDs on the pharmacokinetics of antibiotics in healthy animals [30][31][32][33][34][35][36], studies conducted in the case of disease are limited [37][38][39]. We hypothesized that the effect of meloxicam on the pharmacokinetics of danofloxacin will change with the systemic inflammatory response caused by respiratory infection in lambs, and that the results obtained will contribute to the rational use of danofloxacin.…”
Section: Introductionmentioning
confidence: 99%